Get It Fast, Pay It Later: Analysis of Paylater Features as A Support of The Generation Z Lifestyle - Fauza Husna (Edueksos Jurnal Pendidikan Sosial & Ekonomi, 2023)
ABSTRACTThe paylater feature is a new combination from the times. Currently, paylater is part of the transaction that is popular with many groups, one of which dominates is the younger generation. This transaction is considered practical because it is able to grant the wishes of its users quickly and with minimal obstacles. This study aims to analyze the existence of the paylater feature among Generation Z in fulfilling lifestyles in this modern era. The method used is a qualitative descriptive method or a method that is included in the type of literature research where the authors retrieve data through written data sources and other related sources. The concept of "buy now pay later" in this feature makes it easy for its users to make payments in buying and selling, especially buying and selling online. As time goes by, the lifestyle of Generation Z will continue to improve. This is what makes Generation Z the best target for the presence of the paylater feature, considering that the younger generation has a fairly high level of consumerism. Therefore, this article aims to discuss the existence of paylaters as a support for the lifestyle of Generation Z today. The results of this study indicate that paylaters bring convenience, especially among Generation Z, to be able to quickly grant their wishes at any time, so that paylaters are the best option to support the lifestyle of Generation Z, which is increasingly heterogeneous. Keywords: Paylater, Generation Z, Lifestyle